2014
DOI: 10.1002/ijc.29250
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a two‐stage strategy with HPV testing followed by visual inspection with acetic acid for cervical cancer screening in a low‐income setting

Abstract: The World Health Organization recently advocated a two-stage strategy with human papillomavirus (HPV) testing followed by visual inspection of the cervix with acetic acid (VIA) as a suitable option for cervical cancer screening. However, its accuracy has never been directly assessed in the context of primary screening. To evaluate effectiveness of HPV testing on selfobtained specimens (self-HPV) followed by VIA (sequential testing) in a low-income setting, we recruited 540 women aged between 30 and 65 years in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 43 publications
4
43
1
Order By: Relevance
“…One strength of our study was the low number of patients lost to follow‐up (1.1%). We observed a drastic reduction in loss to follow‐up, compared with the 25% rate in a previous study of HPV‐positive women in Cameroon . Low health literacy, poverty, lack of resources, and geographical conditions are some of the barriers of follow‐up of Cameroonian women.…”
Section: Discussioncontrasting
confidence: 42%
“…One strength of our study was the low number of patients lost to follow‐up (1.1%). We observed a drastic reduction in loss to follow‐up, compared with the 25% rate in a previous study of HPV‐positive women in Cameroon . Low health literacy, poverty, lack of resources, and geographical conditions are some of the barriers of follow‐up of Cameroonian women.…”
Section: Discussioncontrasting
confidence: 42%
“…Sequential screening is a strategy that can increase specificity and, according to the World Health Organisation, is a recommended option in cervical cancer screening(26). However, sequential testing might jeopardise sensitivity(27). In this study, MRI reduced the need for biopsy by 68% in men with PSA ≥3.0 ng/ml (common cut-off for biopsy), but at a cost of lowered sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 13 of the included studies were cohort studies, and 8 reported cross‐sectional findings in eligible populations.…”
Section: Resultsmentioning
confidence: 99%